The right to house room. The confrontation between teachers and the city council of Zaragoza during the Second Republic - Vicente Sánchez, Héctor (Historia y Memoria de la Educación, 2019)
The education law of the 9th of September 1857, commonly known as Moyano's law, granted the right to a house-room for teachers. From this date until the proclamation of the Second Republic, despite the many legal precepts enacted, the enjoyment of this right was not clarified. . The establishment of the republican regime brought new legal dispositions, but the conflicting legislation persisted. Within this large and confusing legal framework, teachers in Zaragoza did battle with the municipal corporation starting at the beginning of the republican period. The city council tried to avoid costs related to this right which implied a significant disbursement, and the educational reform initiated in April 1931 only aggravated the problem. The creation of new education centres and the replacement of religious education increased costs for this right. Against this background, councillors tried to find economic solutions for covering this mandatory cost.